Fluctuation of Monthly Birth Number, By Chance or By Intention - Choi, Seulki (KDI School of Public Policy and Management, 2019)
There are different number of births per month in South Korea. In general, there are more births in January and fewer births in December comparing to the average monthly births of the year. Does it happen by chance or by intention? This study raises three hypotheses for it – 1) random fluctuation, 2) parents’ seasonal preference, and 3) parents’ educational purpose. From the analysis of vital registration data from 1997 to 2018, the most appealing hypothesis was the parents’ educational purpose. The author argues that the opportunity preference was stronger until early 2000 and the path dependency preference after the mid-2000s. Reflecting the rule change of elementary entrance age, the both theories support why January births are preferred by parents. The number of births from other than hospital also imply that there were intentional fabrications of birth registration. But these intentional changes become weaker recently. Especially after the abolition of guarantee of the neighborhood system at the end of 2016, the monthly birth number become stable and looks changing by chance.
Keywords: Monthly Births; Seasonal Changes; Path Dependency Preference; Opportunity Preference